Inverse association between low-density lipoprotein cholesterol and bone mineral density in young- and middle-aged people: The NHANES 2011–2018 - Xiao, Fangjun; Peng, Peng; Gao, Shihua; Lin, Tianye; Fang, Weihua; He, Wei (Frontiers in Medicine, 2022)
Objectives: Low-density lipoprotein cholesterol (LDL-C) play an essential part in bone metabolism. However, the correlation between LDL-C levels and bone mineral density (BMD) is still controversial. This study aims to explore the relationship between LDL-C levels and lumbar BMD in young and middle-aged people. Methods: We conducted a cross-sectional study composed of 4,441 participants aged 20-59 from the National Health and Nutrition Examination Survey (NHANES). LDL-C levels and lumbar BMD were used as independent and dependent variables, respectively. We evaluate the correlation between LDL-C levels and lumbar BMD through a weighted multivariate linear regression model. We performed a subgroup analysis of the relationship between LDL-C levels and lumbar BMD based on age, gender, and body mass index (BMI). Results: After adjusting for confounding factors, LDL-C levels was negatively correlated with lumbar BMD. In subgroup analyses stratified by gender, this negative association was statistically significant in males and females. In the subgroup analysis stratified by age, a negative connection existed in people aged 30-49. In the subgroup analysis divided by BMI), there was an inverse correlation in overweight people (25≤BMI<30). Conclusions: Our research observed an inverse association between LDL-C levels and lumbar BMD in young and middle-aged people, especially in people aged 30-49 and overweight people. Close monitoring of BMD and early intervention may be required for these people.